Control of vortex-induced vibration using a pair of synthetic jets: Influence of active lock-on - Wang, Chenglei (2017)
While conventional vortex-induced vibration (VIV) of bluff bodies is suppressed through reducing the strength of asymmetric vortex shedding, it can also be mitigated by shifting the vortex shedding frequency away from the natural frequency of the body structures using active lock-on. Recently Du and Sun [“Suppression of vortex-induced vibration using the rotary oscillation of a cylinder,” Phys. Fluids 27, 023603 (2015)] utilized periodical rotation to induce the lock-on of the frequency of vortex shedding from a transversely vibrating cylinder to the rotation frequency and demonstrated successful VIV suppression. However, questions were raised from this investigation: Does the occurrence of active lock-on always suppress VIV? If not, how to ensure the appropriate usage of active lock-on for VIV suppression? To address these research questions, a numerical investigation is conducted on the active VIV control of a circular cylinder using a pair of synthetic jets (SJs) at a low Reynolds number of 100. The SJ pair operates with various phase differences over a wide frequency range so that the influence of various lock-on can be investigated. It is found that the VIV control can be affected not only by the occurrence of the primary lock-on but also by the occurrence of other lock-on such as secondary and tertiary lock-on. The occurrence of lock-on does not always result in successful VIV suppression. Sometimes it even causes the augmentation of VIV. Compared to the VIV suppression using the conventional vortex-strength-reduction method, the control by the means of active lock-on seems less effective.